Faktor-Faktor yang Mempengaruhi Negosiasi dan Manajemen Konflik pada Industri Manufaktur dan Industri Makanan Olahan - Fatyandri, Adi Neka; Shofiyah, Shofiy; Fitriana, Aisyah; Fajar, Inayah Alifia; Maharani, Tiara; Valentino, James (Lembaga Publikasi Ilmiah Nusantara, 2023)
The purpose of this research is to analyze the negotiations carried out by 2 large companies, namely the manufacturing industry and the processed food industry. In dealing with conflicts of cultural differences that exist in developing its business. The data analysis method used is the descriptive method of studying literature by collecting library data, reading, taking notes, and processing research materials. The results of the study show that the manufacturing industry and the processed food industry are companies that respect various ethnic and cultural differences in their companies. The culture of negotiation and conflict management within the company also considers several contexts, such as the environmental context and the immediate context. To demonstrate the success of these two companies in overcoming conflict management over cultural differences, these companies have successfully collaborated with several global companies in the world.